Genomic landscape of high-grade meningiomas - Wenya Linda Bi (Nature Portfolio, 2017)
Brain tumors: uncovering genomic disruption in meningiomas Meningiomas, which arise from the tissue surrounding the brain and spinal cord, are the most common primary brain tumor in adults. The majority of these are slow-growing and amenable to surgical resection, if treatment is indicated. However, a subset of aggressive meningiomas are considered high-grade, producing significantly worse mortality. In a first study of its kind, Drs. Wenya Linda Bi, Ian Dunn, Sandro Santagata, Rameen Beroukhim, and colleagues at Harvard Medical School sequenced the genomes of 134 high-grade meningiomas and compared their makeup with lower-grade meningiomas. They found that aggressive tumors were more likely to harbor mutations in the NF2 gene and exhibit widespread genomic disruption. They also harbored an elevated rate of predicted immunogenic mutations, with implications for the use of immuno-modulatory therapies.